Gender effect on underwater undulatory swimming technique of young competitive swimmers - Wadrzyk, L.; Staszkiewicz, R.; Kryst, L.; Zeglen, M. (Acta of Bioengineering and Biomechanics, 2019)
Purpose: The study aim was determining gender-related differences of underwater undulatory swimming (UUS) kinematic indicators and their impact on UUS velocity. Methods: The study included 18 girls (F: age 16.71 ± 0.64 years, FINA points 551 ± 68) and 23 boys (M: age 16.79 ± 0.57 years, FINA points 533 ± 66) training swimming. After marking characteristic anatomical points, subjects performed approximately 7 meters of UUS. A filming device placed behind the underwater window registered the trial. Recordings were analysed using the SkillSpector programme. Results: Boys swam faster (F: 1.24 m/s, M: 1.35 m/s), overcame a greater distance during one cycle (F: 0.67 m, M: 0.74 m), performed movements with higher toes amplitude (F: 0.58 m, M: 0.63 m), obtained higher amplitude and frequency product (F: 1.05, M: 1.15) and smaller ankle joint range of motion (F: 64°, M: 57°). In both groups, relationships between velocity and: maximal ankle joint extension, distance covered during one cycle and backward toes shift during downward movement were found. The results were statistically significant ( p < 0.05). Conclusions: Girls and boys differed in kinematic indicator level, but UUS velocity depends on identical kinematic variables, meaning UUS technical training can be performed without gender-division.